A novel aggregation‐induced emission fluorescent probe with large Stokes shift for sensitive detection of pH changes in live cells. (20th November 2022) - Zhang, Shuwei; Wang, Ting; Wang, Xuewen; Liao, Wenyi; Wang, Xinyao; Yuan, Yu; Chen, Gang; Jia, Xiaodong
Abstract: The detection of intracellular pH is crucial for elucidating the pathological process of cancers, as well as for medical diagnostic applications. Here, we developed an aggregation‐induced emission active pH‐responsive fluorescent probe (TPE‐DCP ) for sensitively detecting cell pH changes. The probe shows obvious pH‐sensing properties at 615 nm, with a pKa value of 6.82 and a good linear pH response ranging from 8.5 to 4.5. TPE‐DCP holds advantages such as excellent anti‐interference performance, good photostability, and low cytotoxicity, and has been successfully used to image intracellular pH changes in cells. Abstract : A novel aggregation‐induced emission active pH‐responsive fluorescent probe (TPE‐DCP ) was developed to detect pH changes in cells sensitively. The probe shows obvious pH‐sensing properties at 615 nm, with a pKa value of 6.82 and a good linear pH response ranging from 8.5 to 4.5. Its advantages, such as excellent anti‐interference performance, good photostability, and low cytotoxicity, enabled it to successfully image intracellular pH changes in live cells.